An overview of the biological activities of less known wild onions (genus Allium sect. Codonoprasum) - Simin, Nataša; Mitić-Ćulafić, Dragana; Pavić, Aleksandar; Orcic, Dejan; Nemes, Ivana; Cetojevic-Simin, Dragana; Mimica-Dukić, Neda (Biologia Serbica, 2020)
Cultivated forms of Allium species, such as onion, garlic, leek and shalot, are widely used in the human diet and are also respected as medicinal plants. In contrast, wild onions, esspecially species from Codonoprasum, are less well known and remain understudied, even though they are present in local diets and traditional medicines. Therefore, in recent years, the chemical composition and biological activities of several species of onions from sect. Codonoprasum have been intensively studied in order to estimate their potential for applications in medicine. Headspace GC–MS analyses revealed that dimethyl-disulfide is by far the most dominant volatile sulfur compound in fresh bulbs of species from Codonoprasum section. LC-MS/MS analysis of phenolic compounds showed that these species are rich in phenolics, particularly in quercetin glycosides and kaempferol 3-O-glucoside. Allium flavum expressed the highest antioxidant activity in common in vitro assays and high anti-inflammatory activity in human platelets. Allium flavum and A. melanantherum exhibited high levels of antigenotoxic effects by activation of cellular antioxidant defence mechanisms. Allium flavum and A. carinatum drastically improved the activity of doxorubicin (Dox) against cancer cells. In zebrafish models, A. flavum and A. carinatum expressed high anti-angiogenic activity and protective effects against Dox-caused cardiac dysfunction and neutropenia. The results of these rewieved studies are indicative of the multiple beneficial pharmacological activities of wild Allium species.